FAKTOR YANG MEMPENGARUHI PEMANFAATAN KELAS IBU HAMIL TAHUN 2018 - Nurul - Hidayah; Toha - Muhaimin; Nurhapipa - - (Sistem Informasi, 2018)
Based on the 2015 Intercensal Population Survey, the maternal mortality rate is still high at 305 per 100,000 live births. One of the efforts to prevent maternal death is through antenatal class activities which are group learning facilities for pregnant women to improve maternal knowledge and skills regarding pregnancy, childbirth, postpartum care and newborns. In Indonesia the antenatal class is still weak in its implementation although it is known to be very likely to reduce maternal mortality. This study aims to determine the factors that influence the class utilization of pregnant women in the work area of Puskesmas Lima Puluh Pekanbaru in 2018. This type of observational analytic quantitative research with cross sectional designe. The study population consisted of 315 third trimester pregnant women with a sample of 104 mothers. Data analysis was carried out in univariate, bivariate and multivariate. The results of the multivariate analysis showed that the variables that were significantly related to the utilization of the antenatal class were knowledge (POR: 4,248; CI 95%: 1,444-12,501), husband's support (POR: 3,707; 95% CI: 1,252-10,975), attitude (POR: 3,479; CI 95%: 1,210-9,997) and support from health workers (POR: 5,367; 95% CI: 1,758- 16,382). It is suggested to health workers to further enhance their role in providing health promotion on the importance of antenatal classes through mass media, electronic media and integrated counseling by establishing cross-program and cross-sectoral cooperation.